2015
DOI: 10.1002/lary.25646
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement of confocal laser endomicroscopy for detection of head and neck neoplasia

Abstract: NA. Laryngoscope, 126:632-637, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
17
0
5
Order By: Relevance
“…Because there is no specific training programme for head and neck cancer, we had to opt for the use of the training programme available for the oesophagus, despite its limitations when extrapolated to the mucosa of the larynx. Moore et al reported an accuracy, sensitivity, specificity, PPV, and NPV of 100% using a similar methodical approach: 29 offline images and 6 video sequences 27 . Oetter et al 17 investigated the value of pCLE in the classification of lesions of the oral mucosa and suggested a classification and scoring system to facilitate the interpretation of these images by examiners without prior experience in this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is no specific training programme for head and neck cancer, we had to opt for the use of the training programme available for the oesophagus, despite its limitations when extrapolated to the mucosa of the larynx. Moore et al reported an accuracy, sensitivity, specificity, PPV, and NPV of 100% using a similar methodical approach: 29 offline images and 6 video sequences 27 . Oetter et al 17 investigated the value of pCLE in the classification of lesions of the oral mucosa and suggested a classification and scoring system to facilitate the interpretation of these images by examiners without prior experience in this technique.…”
Section: Discussionmentioning
confidence: 99%
“…OCT can delineate the internal structure of tissue by analyzing back-scattered light obtained from a tissue using an optical interferometer [45]. Moreover, pCLE can observe the tissue structure and vasculature of oral mucosa lesions in real time [46]. Therefore, ALA-PDD in combination with OCT and pCLE might clarify alternatives of cell metabolism and the tissue structure of oral mucosa lesions, thereby improving the diagnostic accuracy.…”
Section: Issues and Future Perspectivesmentioning
confidence: 99%
“…Low sensitivity was reported when sections had positive or close final margins and was mainly explained by incorrect sampling of the tumor bed or in resected specimens compared with final standard histology. Today, alternative intraoperative methods to improve tumor margins in head and neck surgery, such as Raman spectroscopy or endomicroscopy, are under investigation in preclinical and clinical studies [7,13,14]. In addition to their technical capabilities, these methods must also be considered according to the duration of the procedure, tumor location, and procedure cost.…”
Section: Introductionmentioning
confidence: 99%